Estudo do efeito do envelhecimento eletroquímico em filmes de poli(3-hexiltiofeno) - Gonçalves, Roger (2014)
The study of the electrochemical aging of conductive polymers, including of polythiophenes, has been described in the literature. However, this paper proposed study, in addition to electrochemical aging of polyethylene films (3-hexylthiophene), the influence of synthesis variables on the initial electrochemical properties of the films and also how they affect the degradation process. This study was conducted using factorial designs 23, in which the variables were the concentration of monomer (3- hexylthiophene), electrolyte concentration (LiClO4) and the presence of water, on two levels. To estimate the effect were used for responses the parameters of cyclic voltammetry, the impedance spectra and the Mott-Schottky curves. The model of transmission lines for porous electrodes where used for fit the impedance spectra. It has been shown that the changes observed are related to modifications in film/solution interface, because the parameters of impedance spectra have undergone major changes. It was also possible to assess the variables affect the synthesis not only the initial parameters as well as the extent of degradation that the polymer undergoes, including, identifying two stages of degradation. The first stage occurs before 120 min, and that in most of the films has a rate of change of the parameters marked. The second time, with slightly larger gear change occurs after this time. There is a relationship between the initial parameters and the evolution of degradation. In general, the films with improved initial properties have lower resilience to the degradation process, while the films with lower values of initial properties have shown less variation in these parameters over the same process.